Use of medications and pharmaceutical monitoring in the treatment of patients with fibromyalgia (Research, Society and Development, 2021)
This research aims to understand how pharmaceutical follow-up can help in the treatment of fibromyalgia, taking into account the main types of drug treatments and the role of the pharmacist. This is an integrative review, where data collection was performed with articles between 2016 to 2021 in the following databases: Latin American and Caribbean Literature on Health Sciences (LILACS), Publisher Medline (PUBMED), Scientific Electronic Library Online (SciELO), using the following descriptors and keywords: Fibromyalgia, Pain, Medicines and Treatment. Through the results obtained, it was found that the best option for the treatment of fibromyalgia is the combination of pharmacological and non-pharmacological interventions, with an emphasis on combined treatments with drugs aimed at multiple molecular mechanisms, as predicted by the Federal Council of Pharmacy. Through the data discussed, it can be concluded that the combination of psychological and physical therapy and the use of drugs is the best option for the treatment of patients with fibromyalgia. In this sense, pharmacology contributes with medications with the purpose of reaching the central pain pathways, favoring the patient and reducing their daily affliction. However, even so, further research is needed on treatment alternatives for this complex condition.